Simulation of Electrical Interaction of Cardiac Cells - Heppner, Dennis B. (1970)
A model of the electrical activity of excitable membrane was used to simulate action potential propagation in cardiac cells. Using an implicit method for solving finite difference equations, propagation through the intercalated disc region between two abutting cells was studied. A model of interaction was constructed and parameters of the cellular junction determined. Estimates of the intercalated disc resistance were then made from these junction parameters using a field analysis of the junction. Values of approximately 4 Ω-cm(2) were found and correlate well with experimentally measured values.